PERMASALAHAN KEPEMIMPINAN PEREMPUAN DALAM AL-QURAN DAN SUNNAH: ANTARA TEOLOGIS DAN POLITIS - A. Latif, Hamdiah (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2019)
The issue of women's leadership in the public sphere is still debatable. The majority of Muslim scholars reject the leadership with various reasons and proofs, both revelation (naqliy) and reason (‘aqliy). This paper would like to discuss and invite a review of issues that have not yet completely elaborated between the theological threads and political elements that often descend upon issues of women's leadership at the level of reality presented